Water quality of Parit Belanda River based on physical-chemical parameters, Rumbai Pesisir District, Pekanbaru City, Riau Province - Yudi Asriansyah; Madju Siagian; Asmika H Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The area around the Parit Belanda Riverhas been used by human activity. Remains of the activity may enter the water and decrease the water quality of the river. To understand the water quality of the Parit Belanda River, a research was conducted in March-April 2016. There were three sampling stations namely Station 1 in up stream, Station 2 in the middle of the stream, and Station 3 in down stream. Samplings were conducted 4 times, once/week.Water quality parameters measured were temperature, transparency, velocity, pH,DO,CO2,nitrate and phosphate.Results shown that temperature: 29-30oC, pH : 5, DO:3.15-3.96 mg/L, CO2: 22.98-56.93mg/L,velocity : 0.9-0.27 cm/second, transparency: 30.75-38.75 cm, nitrate: 0.13-0.21 mg/L, and phosphate 0.25-0.33 mg/L. Nitrate concentration indicate that the Parit Belanda River was categorized as oligotrophic, but base on phosphate concentration indicate that the Parit Belanda River is mesotrophic.Keywords : River , Parit Belanda River, Water Quality, oligotrophic, mesotrophic